Melanoma and use of sunscreens. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2002)
In the 60’s sunscreens did not yet exist. The protection against the side effects of sun radiations mainly relied on the clothes, rational exposure and fear of burning. There were only tanning lotions and oils after sun bathing, which were produced by the cosmetic industry, whereas the drug industry was apparently not interested in this market. Only dermatologists knew that squamous cell and basal cell carcinomas were due to the side effects of sun radiations. However, they did not believed that melanoma was clearly related to sun exposure. Common people did not know anything about the relationship between sun and skin malignancy and the panic of nevi did not exist. A widely diffuse prejudice talked about “nevi should not be touched”. Also due to this prejudice, at that time nevi were not easily removed. (...).